The iAnimal Film Series: Activating Empathy Through Virtual Reality. Issue 1 (1st June 2021) - Cecil, Holly
Abstract: This article explores the innovative use of virtual reality (VR) technology in nonfiction documentary film formats by animal-advocacy organizations. I examine the potential of the VR medium to communicate the living and dying environments of factory-farmed animals, and to generate viewer empathy with the animal subjects in their short, commodified lives from birth to slaughterhouse. I present a case study of the iAnimal short film series produced by Animal Equality, which made its public debut at the 2016 Sundance Film Festival. Employing a critical animal studies framework, I engage Kathryn Gillespie's work on witnessing of the nonhuman condition as a method of academic research, and apply to it the embodied experience of virtual witnessing through virtual realty.